Anthocyanin profile of strawberry fruit as affected by extraction conditions - Karaaslan, Nagihan M.; Yaman, Mehmet (Taylor & Francis Inc, 2018)
The purpose of the study was to investigate the effect of extraction conditions to determine anthocyanin compounds in strawberry fruit. Anthocyanin profile of this fruit were determined via high-performance liquid chromatography-electrospray ionization-mass spectrometry. Flow rate of mobile phase, fragmentor potential, injection volume, and column temperature were applied to be optimum values as 0.5mL min(-1), 110V, 5 mu L, and 30 degrees C, respectively. The extraction process was the important step in the isolation and identification of anthocyanins. For this purpose, anthocyanin contents in strawberry fruit were examined in terms of solvent type, extraction time, and liquid:solid ratio (v:w). The best extraction conditions in this fruit were found to be methanol as solvent, 30min as extraction time and 1:1 as liquid:solid ratio (v:w). The results showed that the anthocyanin contents of strawberry fruit change by altering extraction conditions.
Keywords: Anthocyanin; Extraction; Strawberry fruit; High-performance liquid chromatography-electrospray ionization-mass spectrometry (HPLC-ESI-MS)